The efficacy of artesunate in animal models of sepsis: a systematic review and meta-analysis - Xie, Wenzhan; Lv, Linxi; Wang, Tian; Wei, Jialong; Gui, Yanshan; Han, Bing; Zhou, Laixian; Feng, Hui; Gu, Wei (Frontiers in Pharmacology, 2026)
BackgroundSepsis is a life-threatening condition caused by a dysregulated host response to infection, characterized by biphasic immune dysregulation and high mortality rates. Artesunate (AS), a semisynthetic artemisinin derivative, has demonstrated broad pharmacological properties, yet its overall efficacy and mechanisms in sepsis remain systematically unassessed at the preclinical level.ObjectivesIn this study, we aimed to conduct the first systematic review and meta-analysis to evaluate the therapeutic efficacy and underlying mechanisms of AS in animal models of sepsis.MethodsWe systematically searched five electronic databases up to 3 September 2025, for controlled in vivo studies analyzing the effects of AS in septic animals. The study quality was assessed using the SYRCLE risk-of-bias tool, and evidence certainty was rated via the GRADE approach. Statistical analyses, including meta-analysis, publication bias, and sensitivity analyses, were performed using RevMan 5.4 and Stata 17.0.ResultsFifteen studies involving mice and rats were included. Meta-analysis indicated that AS was associated with improved survival (10 studies, OR: 6.87, 95% CI: 3.81–12.41, p < 0.00001), reduced bacterial load, and promotion of body weight recovery. Organ protection was evidenced by attenuated lung injury (reduced histological scores, MPO activity, and wet-to-dry ratio) and improved liver function (decreased AST and ALT levels). Analysis of cytokine data from different time-points suggested a potential phase-dependent immunomodulatory effect: AS suppressed pro-inflammatory cytokines (TNF-α and IL-6) during the hyperinflammatory phase while restoring immune competence in the immunosuppressive phase, accompanied by elevated IL-1β. Furthermore, AS reduced apoptosis (decreased TUNEL-positive cells) and enhanced pro-survival signaling (increased p-mTOR/mTOR ratio); however, its effect on caspase-3 was not significant. Sensitivity analyses supported the robustness of the primary findings, and no significant publication bias was detected within the limits of the available studies.ConclusionAS is associated with survival benefits and multi-organ protection in septic animal models through multimodal mechanisms, potential phase-aware immunomodulation, antiapoptotic effects, and enhanced bacterial clearance. Despite methodological heterogeneity across studies, these preclinical findings support further investigation of AS as a potential therapeutic candidate for sepsis treatment.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251146068.